A comparison of the effects of temporary hippocampal lesions on single and dual context versions of the olfactory sequence memory task - Sill, Orriana C; Smith, David M (Behavioral neuroscience, 2012)
In recent years, many animal models of memory have focused on one or more of the various components of episodic memory. For example, the odor sequence memory task requires subjects to remember individual items and events (the odors) and the temporal aspects of the experience (the sequence of odor presentation). The well-known spatial context coding function of the hippocampus, as exemplified by place cell firing, may reflect the "where" component of episodic memory. In the present study, we added a contextual component to the odor sequence memory task by training rats to choose the earlier odor in one context and the later odor in another context and we compared the effects of temporary hippocampal lesions on performance of the original single context task and the new dual context task. Temporary lesions significantly impaired the single context task, although performance remained significantly above chance levels. In contrast, performance dropped all the way to chance when temporary lesions were used in the dual context task. These results demonstrate that rats can learn a dual context version of the odor sequence learning task that requires the use of contextual information along with the requirement to remember the "what" and "when" components of the odor sequence. Moreover, the addition of the contextual component made the task fully dependent on the hippocampus.